Pengaruh Model Project Based Learning Terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas IV Sekolah Dasar - Christiananda, FR.; Suwartini, Sri; Rahmawati, Isna (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to examine the influence of the Project-Based Learning (PjBL) model on the learning outcomes of fourth-grade students at SDN Karang Wedi in the subject of Pancasila Education, particularly on the topic of socio-cultural differences.Method – The research method used a quasi-experimental design with a quantitative approach was employed. The sample in this study was class fourth-grade students. Data were collected through observation, pre-tests and post-tests, as well as documentation. The data were analyzed using normality tests, homogeneity tests, and t-tests. Findings – The results showed a significant improvement in students’ learning outcomes after the implementation of the PjBL model. The t-test shows a significance value of 0.0001 < 0.05. As indicated by a t-value of 3.967, which exceeds the t-table value of 2.010. In the pretest and posttest activities, there was a significant improvement. Research Implications – The practical implication of this research shows that the PjBL model is effective in enhancing students’ understanding of Pancasila Education and is recommended for broader application in the learning process.